TARAS SHEVCHENKO AND KAROL’ LIPINS’KYI: INTERNATIONAL ARTISTIC RELATIONS - Bakhtalovs’ka, O. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article highlights Polish-Ukrainian cultural-artistic interrelations imprinted in the creations by poet Taras Shevchenko and composer Karol’ Lipins’kyi; reveals peculiar features of their mutual unity.